Incidence and general hospital costs of self-harm across England: estimates based on the multicentre study of self-harm. (12th March 2020) - Tsiachristas, Apostolos; Geulayov, Galit; Casey, Deborah; Ness, Jennifer; Waters, Keith; Clements, Caroline; Kapur, Nav; McDaid, David; Brand, Fiona; Hawton, Keith
Abstract: Aims: The aim of this study was to estimate incidence of self-harm presentations to hospitals and their associated hospital costs across England. Methods: We used individual patient data from the Multicentre Study of Self-harm in England of all self-harm presentations to the emergency departments of five general hospitals in Oxford, Manchester and Derby in 2013. We also obtained cost data for each self-harm presentation from the hospitals in Oxford and Derby, as well as population and geographical estimates from the Office for National Statistics. First, we estimated the rate of self-harm presentations by age and gender in the Multicentre Study and multiplied this with the respective populations to estimate the number of self-harm presentations by age and gender for each local Clinical Commissioning Group (CCG) area in England. Second, we performed a regression analysis on the cost data from Oxford and Derby to predict the hospital costs of self-harm in Manchester by age, gender, receipt of psychosocial assessment, hospital admission and type of self-harm. Third, the mean hospital cost per age year and gender were combined with the respective number of self-harm presentations to estimate the total hospital costs for each CCG in England. Sensitivity analysis was performed to address uncertainty in the results due to the extrapolation of self-harm incidence and cost from the Multicentre Study to England. Results: There were 228 075 estimated self-harm presentations (61% were female) by 159 857 patients in 2013 in England. The largest proportions of self-harm presentations were in the age group 40–49 years (30%) for men and 19–29 years (28%) for women. Associated hospital costs were approximately £128.6 (95% CI 117.8−140.9) million in 2013. The estimated incidence of self-harm and associated hospital costs were lower in the majority of English coastal areas compared to inland regions but the highest costs were in Greater London. Costs were also higher in more socio-economically deprived areas of the country compared with areas that are more affluent. The sensitivity analyses provided similar results. Conclusions: The results of this study highlight the extent, hospital costs and distribution of self-harm presentations to hospitals in England and identify potential sub-populations that might benefit from targeted actions to help prevent self-harm and assist those who have self-harmed. They can support national as well as local health stakeholders in allocating funds and prioritising interventions in areas with the greatest need for preventing and managing self-harm.